Advances in prognostic biomarkers for esophageal cancer. (1st February 2019) - Yang, Wanli; Han, Yu; Zhao, Xinhui; Duan, Lili; Zhou, Wei; Wang, Xiaoqian; Shi, Gaokai; Che, Yinggang; Zhang, Yujie; Liu, Jinqiang; Zhang, Hongwei; Zhao, Qingchuan; et al.
ABSTRACT: Introduction : Esophageal cancer (EC) is one of the deadliest neoplasms in Asian countries. The high mortality rate and low survival rate of this disease are the major challenges for patients. Therefore, exploring novel biomarkers for prognosis analysis is still an important task for cancer research. Areas covered : The aim of our review is to summarize the recent advances in prognostic markers for EC. We also discuss the pros and cons of different types of biomarkers for improving the judgment of prognosis. These biomarkers mainly include liquid biopsy, genomics biomarkers, and proteomic molecules. In this sense, we found that liquid biopsies, especially circulating tumor cells, should be fully considered in clinical practice, as they show high specificity and accuracy. Proteomic biomarkers also show potential value, but the costs of associated techniques may be expensive for routine use. Alternatively, epigenetic markers (such as miRNAs) appear to be very promising since they can be easily detected in both tissues and bodily fluids. Expert commentary : So far, the defined and available biomarkers for prognosis judgment of EC are insufficient. Future studies and clinical trials should be carried out to improve the clinical use of the biomarkers discussed here.